Highly efficient extraction of lead ions from smelting wastewater, slag and contaminated soil by two-dimensional montmorillonite-based surface ion imprinted polymer absorbent. (October 2018) - Zhu, Chao; Hu, Tianjue; Tang, Lin; Zeng, Guangming; Deng, Yaocheng; Lu, Yue; Fang, Siyuan; Wang, Jingjing; Liu, Yani; Yu, Jiangfang
Abstract: The rapid, efficient and selective extraction of heavy metal ions is significant for wastewater pretreatment and metal ion recycle. Using montmorillonite as the template substrate and Pb 2+ as template ions, a novel two-dimensional montmorillonite-based surface ion imprinted polymer (IIP-MMT) adsorbent is successfully synthesized via activators generated by electron transfer for atom transfer radical polymerization (AGET-ATRP). Batch adsorption experiments are performed to assess the properties of the imprinted polymer sorbent, along with its selectivity and reusability in practical extraction of Pb 2+ . It is interesting that the crosslinking density of the imprinted polymer has impact on the sorption property, where suitable density is coupled with the highest adsorption capacity and the best selectivity. Benefiting from the surface-imprinting technique and AGET-ATRP, IIP2-MMT is proved to own a highly effective Pb 2+ adsorption capacity to reach 158.68 mg/g within 30 min, where the corresponding maximum adsorption capacity is 201.84 mg/g. Moreover, this material exhibits satisfactory stability and reusability that the high adsorptive capability of IIP-MMT retains more than 95% after six cycles. Thus, it is expected to reduce the wastewater disposal expenses. Besides, owing to the characteristics of PHEMA brushes and SHA chelating ligand, IIP-MMT has strong anti-interference and anti-blockage abilities to extract Pb 2+ from smelting wastewater, slag and contaminated soil. Considering the low cost, excellent stability, high extraction efficiency, environmental friendliness, it is expected that the proposed material is very promising for treatment of heavy metals-contaminated wastewaters and soil, or ion recycle. Graphical abstract: Image 1 Highlights: Two-dimensional IIP-MMT adsorbent with large specific surface area and low mass transfer resistance. AGET-ATRP was used for Pb 2+ imprinted polymer preparation. The crosslinking density of the polymer influenced the sorption property. IIP-MMT possessed high adsorption efficiency and selectivity towards Pb 2+ . IIP-MMT exhibited excellent effect and satisfactory stability, reusability in real samples.